Degradation method of mixed waste plastic
By using the pre -reduction catalyst in a fixed bed reactor, the program temperature and degradation of the mixed waste plastic solve the problem of pre -separation difficulty and CL atomic poisoning during the recovery process, and achieve efficient plastic recycling and environmental protection.
Patent Information
- Application Number
- CN202310889927.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
Smart Images

Figure CN119330305A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic intermediate synthesis, and in particular to a method for degrading mixed waste plastics. Background Art
[0002] Since its introduction, plastics have been widely used in various fields of the national economy, bringing great convenience to human production and life. However, its huge usage and waste have led to increasingly serious environmental pollution. The recycling and reuse of waste plastics has become a major issue concerning the ecological environment and the fate of mankind.
[0003] At present, the recycling of waste plastics is still mainly concentrated on pyrolysis and hydrogenolysis, except for physical methods such as incineration and landfill. The known pyrolysis and hydrogenolysis methods have the problem that they cannot achieve the recycling of multi-component mixed plastics and the catalysts in the current recycling methods have poor tolerance to the Cl element of polyvinyl chloride (PVC) in mixed waste plastics. Therefore, how to recycle plastics without separating mixed waste plastics has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0004] The purpose of this application is to provide a method for degrading mixed waste plastics to solve the problems of pre-separation and poisoning of catalysts by Cl atoms in the recycling process of mixed waste plastics. The specific technical solution is as follows:
[0005] The present application provides a method for degrading mixed waste plastics, comprising the following steps:
[0006] (1) After pre-reduction treatment of the catalyst, the catalyst and mixed waste plastics are added into a fixed bed reactor;
[0007] (2) Under a reducing gas, controlling the temperature of a fixed bed reactor by temperature programming to obtain a degradation product;
[0008] Among them, the mixed waste plastics include polyvinyl chloride; the reducing gas includes hydrogen and argon, based on the volume of the reducing gas, the volume percentage of hydrogen is 10%-100%, and the volume percentage of argon is 0%-90%; the heating rate of the fixed bed reactor at 150℃-350℃ is 1℃ / min-5℃ / min.
[0009] In addition to polyvinyl chloride, mixed waste plastics may also include polyolefins, polystyrene or polyethylene terephthalate, etc. The above steps are used to degrade the mixed waste plastics. By controlling the heating rate and temperature of the fixed bed reactor, the mixed waste plastics without the pre-separation step are subjected to polyvinyl chloride dechlorination, dechlorinated polyvinyl chloride hydrogenolysis, polyolefin hydrogenolysis and polyethylene terephthalate hydrogenolysis under the action of the catalyst. The specific reaction equation is shown in (1):
[0010] CO x Cl y H z +(2+x+y / 2-z / 2)H2=CH4+xH2O+yHCl (1)
[0011] The mixed waste plastics are converted into usable methane (CH4) and hydrogen chloride (HCl), and water vapor (H2O) is released. The mixed waste plastics do not go through a pre-separation step and still have a high yield and conversion rate, and the poisoning of the Cl atoms in the polyvinyl chloride to the catalyst is reduced, reducing the pollution to the environment.
[0012] The present application does not particularly limit the type of fixed bed reactor, and those skilled in the art can select it according to actual conditions, as long as the purpose of the present application can be achieved. For example, the fixed bed reactor can be an adiabatic fixed bed reactor, a multi-stage adiabatic fixed bed reactor, a tubular fixed bed reactor or an autothermal reactor.
[0013] In one embodiment of the present application, the catalyst is selected from any one of Pt / TiO2, Ru / Al2O3, Ru / TiO2, Ru / CeO2, Ru / SiO2, Ir / Al2O3, Ir / TiO2 or Ir / SiO2. The present application has no particular restrictions on the metal loading in the above-mentioned catalyst, as long as the purpose of the present application can be achieved. For example, based on the mass of the oxide carrier, the loading of Pt / Ru / Ir is 0.1%-5%. The above-mentioned types of catalysts can be used to catalyze hydrogenolysis of mixed waste plastics to obtain degradation products, which is beneficial to the degradation and conversion of mixed waste plastics. Among them, the oxide carrier refers to the oxide in the above-mentioned catalyst, for example, the oxide carrier in Pt / TiO2 refers to TiO2, and the oxide carrier in Ru / Al2O3 refers to Al2O3.
[0014] In one embodiment of the present application, the catalyst is Ru / TiO2, and the loading amount of Ru in Ru / TiO2 is 0.1%-5% based on the mass of TiO2. When the catalyst Ru / TiO2 is selected, the yield of CH4 and HCl generated by the catalytic reaction of mixed waste plastics is higher.
[0015] The present application has no particular restrictions on the preparation method of the catalyst, as long as the purpose of the present application can be achieved. For example, the preparation method of the catalyst may include but is not limited to the following steps:
[0016] The metal salt is used as a precursor, and the metal salt and the oxide carrier are weighed according to the metal loading amount. The metal salt is dissolved in water and magnetically stirred to form a precursor solution; then the oxide carrier is added to the precursor solution and magnetically stirred to obtain a suspension. The obtained suspension is evaporated to dryness and then dried to obtain a solid. After the obtained solid is ground, it is placed in a muffle furnace for roasting to obtain a catalyst.
[0017] Those skilled in the art can select the types of the above-mentioned metal salts and oxide carriers according to actual conditions. For example, when preparing Ru / TiO2, the metal salt can be RuCl3·H2O or ruthenium acetylacetonate, and the oxide carrier can be TiO2; when preparing Pt / TiO2, the metal salt can be H2PtCl6 or Pt(NO3)2, and the oxide carrier can be TiO2; when preparing Ru / Al2O3, the metal salt can be RuCl3·H2O or ruthenium acetylacetonate, and the oxide carrier can be Al2O3; when preparing Ru / CeO2, the metal salt can be RuCl3·H2O or ruthenium acetylacetonate, and the oxide carrier can be Al2O3. H2O or ruthenium acetylacetonate, the oxide carrier is CeO2; when preparing Ru / SiO2, the metal salt can be RuCl3·H2O or ruthenium acetylacetonate, and the oxide carrier is SiO2; when preparing Ir / Al2O3, the metal salt can be IrCl3 or H2IrCl6, and the oxide carrier is Al2O3; when preparing Ir / TiO2, the metal salt can be IrCl3 or H2IrCl6, and the oxide carrier is TiO2; when preparing Ir / SiO2, the metal salt can be IrCl3 or H2IrCl6, and the oxide carrier is SiO2. This application has no special restrictions on the conditions for drying, as long as the purpose of this application can be achieved. For example, the drying temperature is 60℃-150℃, and the drying time is 2h-24h. This application has no special restrictions on the roasting conditions of the muffle furnace, as long as the purpose of this application can be achieved. For example, the heating rate of the muffle furnace is 1°C / min-5°C / min, the maximum heating temperature of the muffle furnace is 300°C-600°C, and the calcination time of the muffle furnace is 1h-6h.
[0018] In one embodiment of the present application, the mixed waste plastics further include at least one of polyolefin, polystyrene or polyethylene terephthalate. The present application has no particular restrictions on the type of polyolefin, as long as the purpose of the present application can be achieved. For example, the polyolefin is linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), high-density polyethylene (HDPE), homopolymer polypropylene (HOMOPP), copolymer polypropylene (COPP), etc.
[0019] The present application has no particular restrictions on the size of the particles of the mixed waste plastics during the degradation process, as long as the purpose of the present application can be achieved. For example, when the mass of a single particle of the mixed waste plastics to be degraded is greater than 6g, it can be cut into particles with a single particle mass less than or equal to 0.01g, or a particle diameter less than 60 mesh, so as to allow for sufficient reaction.
[0020] In one embodiment of the present application, based on the mass of the mixed waste plastics, the mass percentage of polyvinyl chloride is 25%-100%. When the mass percentage of polyvinyl chloride in the mixed waste plastics is within the above range, the programmed temperature degradation method of the mixed waste plastics of the present application is beneficial to reduce the poisoning of the Cl atoms in the polyvinyl chloride to the catalyst and reduce the pollution to the environment.
[0021] In one embodiment of the present application, the mass ratio of the catalyst to the mixed waste plastics is 1:(1-5). When the mass ratio of the catalyst to the mixed waste plastics is within the above range, the mixed waste plastics can achieve a greater degree of degradation and conversion under the action of the catalyst.
[0022] In one embodiment of the present application, in step (1), the step of pre-reducing the catalyst comprises: before using the catalyst, placing the catalyst in a reaction gas at 200°C-500°C for reduction for 2h-6h; the reaction gas is selected from hydrogen or diluted hydrogen. The catalyst pre-reduced through the above steps has hydrogenolysis ability and can be used in the degradation reaction of mixed waste plastics to show excellent reaction activity, so that the mixed waste plastics have excellent conversion rate and the degradation product has a high yield.
[0023] In one embodiment of the present application, based on the volume of the diluted hydrogen, the volume percentage of hydrogen is 10%-90%, and the volume percentage of argon is 10%-90%. Selecting the diluted hydrogen within the above volume distribution range is conducive to the reduction of the metal on the catalyst surface and has hydrogenolysis ability.
[0024] In one embodiment of the present application, after step (2), the catalyst is taken out from the fixed bed reactor and reused in step (1). Specifically, it can be understood that after the previous degradation reaction is completed, since the products after the degradation of the waste mixed plastics are mostly gas, the separation only requires taking out the catalyst from the fixed bed reactor, and then recycling the taken out catalyst in the degradation reaction of the waste mixed plastics. This shows that the catalyst of the present application has good cyclic stability and can be recycled in the degradation of waste mixed plastics.
[0025] In one embodiment of the present application, the pressure of the reducing gas is 50 kPa-150 kPa. Controlling the pressure of the reducing gas within the above range is beneficial to the degradation and conversion reaction of the mixed waste plastics.
[0026] In one embodiment of the present application, the degradation product includes at least one of HCl, CH4, NH3 or H2O.
[0027] Beneficial effects of this application:
[0028] The present application provides a method for degrading mixed waste plastics, which comprises the following steps: after pre-reducing the catalyst, adding the catalyst and the mixed waste plastics into a fixed bed reactor; controlling the temperature of the fixed bed reactor by programmed temperature rise under a reducing gas to obtain degradation products; wherein the mixed waste plastics include polyvinyl chloride; the reducing gas includes hydrogen and argon, based on the volume of the reducing gas, the volume percentage of hydrogen is 10%-100%, and the volume percentage of argon is 0%-90%; the fixed bed reactor is heated at a temperature of 150°C-350°C at a rate of 1°C / min-5°C / min. The mixed waste plastics are degraded by the above steps, which effectively solves the problems of pre-separation and poisoning of the catalyst by Cl atoms in the recycling process of the mixed waste plastics. The mixed waste plastics are degraded by the above steps, and the mixed waste plastics have an excellent conversion rate and the degradation products have a high yield.
[0029] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0031] Figure 1 The product yield and selectivity diagram of the catalyst 1%Ru / TiO2 using the programmed temperature degradation method of the present application for 9 cycles;
[0032] Figure 2 The product yield and selectivity of the catalyst 1%Ru / TiO2 with 40℃ / min heating to 200℃ for 9 cycles;
[0033] Figure 3 The product yield and selectivity of the catalyst 1%Ru / TiO2 with 9 cycles of heating from 40℃ / min to 250℃;
[0034] Figure 4 The product yield and selectivity diagram of the catalyst 1%Ru / TiO2 using 40℃ / min to 300℃ cycle for 9 times. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0036] Example
[0037] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.
[0038] Test methods and equipment
[0039] The reaction systems of the embodiments and comparative examples were qualitatively and quantitatively analyzed by gas chromatography.
[0040] Calculation of conversion rate
[0041] Conversion rate = 100% - the number of moles of remaining mixed waste plastics / the number of moles of input mixed waste plastics × 100%.
[0042] Among them, for a single type of plastic, the molar number is the molar number corresponding to the monomer of its polymer. During the experiment, the mixed waste plastics were weighed separately for each plastic and then mixed. The molar number of mixed waste plastics put into the mixed waste plastics was the sum of the molar numbers of several plastics put in, and the molar number of the remaining mixed waste plastics was the sum of the molar numbers of several plastics remaining after degradation was completed.
[0043] Calculation of CH4 and HCl production
[0044] During the degradation reaction, a gas collection bag is used to collect gas from the gas outlet of the fixed bed reactor, and the gas is detected by a flame ionization detector (FID) and a thermal conductivity detector (TCD) in a gas chromatograph. The yield of CH4 or HCl is calculated based on the chromatographic peak area and corresponding response factor of CH4 or HCl, as well as the Ar internal standard response factor.
[0045] Calculation of the yield of CH4 and HCl
[0046] The yield is the ratio of the actual output of the product obtained from a unit amount of mixed waste plastics to the theoretically calculated maximum output of the product obtained from a unit amount of mixed waste plastics.
[0047] Taking CH4 as an example, CH4 yield = actual CH4 mole number obtained / theoretical maximum CH4 mole number × 100%; wherein, the theoretical maximum CH4 mole number is the mole number of carbon atoms in the mixed waste plastics.
[0048] Calculation of CH4 selectivity
[0049] CH4 selectivity = actual CH4 mole number obtained / (actual CH4 mole number obtained + mole number of higher carbon number hydrocarbon products × corresponding carbon atom number);
[0050] A higher carbon number refers to a carbon number greater than or equal to 2.
[0051] Catalyst cycle stability test
[0052] The catalyst Ru / TiO2 was used for the cycle stability test. After the first degradation reaction, the catalyst Ru / TiO2 was taken out, and then the catalyst Ru / TiO2 was pre-reduced, and then mixed with new mixed waste plastics and put into the fixed bed reactor. Repeat the above steps and end after 9 cycles. During the degradation reaction, a gas collection bag was used to collect gas from the gas outlet of the fixed bed reactor, and a new gas collection bag was replaced after each cycle. The above calculation method was used to calculate the yield and selectivity of CH4 and HCl collected after each degradation reaction.
[0053] Example 1
[0054] <Preparation of Ru / TiO2 Catalyst>
[0055] Take Ru metal salt RuCl3·H2O as the precursor, weigh 0.05g of the metal salt RuCl3·H2O and 2g of the oxide carrier TiO2 according to the metal loading of 1%, dissolve the metal salt RuCl3·H2O in 5mL of water, and stir magnetically at 200rpm for 30min to form a precursor solution;
[0056] Then, 2g of oxide carrier TiO2 was added to the precursor solution and magnetically stirred at 200rpm for 24h to obtain a suspension. The obtained suspension was evaporated to dryness at 60℃, -0.1MPa vacuum, 120rpm, and then dried at 60℃ for 24h. After the obtained solid was ground, it was heated to 400℃ in a muffle furnace at a heating rate of 2℃ / min and calcined for 2h to obtain 2g of catalyst Ru / TiO2.
[0057] <Pre-reduction of catalyst>
[0058] 1 g of the catalyst Ru / TiO2 was placed in a reaction gas and reduced at 300° C. for 4 h. The reaction gas was diluted hydrogen, and based on the volume of the diluted hydrogen, the volume percentage of hydrogen was 10% and the volume percentage of argon was 90%.
[0059] <Degradation of mixed waste plastics>
[0060] In a fixed bed reactor (manufacturer: Beijing Zhongshi Yida Technology Co., Ltd., model ZSYD-102), 1 g of the catalyst Ru / TiO2 and 2 g of mixed waste plastics after the above-mentioned pre-reduction treatment were added, and the fixed bed reactor was heated from room temperature to 150°C at a rate of 40°C / min under a hydrogen atmosphere with a pressure of 100 kPa. The temperature of the fixed bed reactor was controlled by programmed temperature heating, and the temperature was increased from 150°C to 350°C at a rate of 3°C / min, and then the temperature was stopped, and the fixed bed reactor was closed to obtain degradation products CH4 and HCl.
[0061] Example 2
[0062] <Preparation of catalyst Ru / TiO2> and <Pre-reduction of catalyst> are the same as in Example 1.
[0063] <Degradation of mixed waste plastics>
[0064] Except that the heating rate was changed from 3°C / min to 1°C / min, the rest was the same as Example 1.
[0065] Example 3
[0066] <Preparation of catalyst Ru / TiO2> and <Pre-reduction of catalyst> are the same as in Example 1.
[0067] <Degradation of mixed waste plastics>
[0068] Except that the heating rate was changed from 3°C / min to 5°C / min, the rest was the same as Example 1.
[0069] Example 4
[0070] <Preparation of Ru / TiO2 Catalyst>
[0071] Except for weighing 0.005 g of metal salt RuCl3·H2O according to the metal loading amount of 0.1%, the rest is the same as Example 1 to prepare 2 g of catalyst Ru / TiO2.
[0072] <Pre-reduction of catalyst>
[0073] The process is the same as that of Example 1 except that 1% Ru / TiO2 is replaced by 0.1% Ru / TiO2.
[0074] <Degradation of mixed waste plastics>
[0075] The process is the same as that of Example 1 except that 1% Ru / TiO2 is replaced by 0.1% Ru / TiO2.
[0076] Example 5
[0077] <Preparation of Ru / TiO2 Catalyst>
[0078] Except for weighing 0.1 g of metal salt RuCl3·H2O according to the metal loading of 2%, the rest is the same as Example 1 to prepare 2 g of catalyst Ru / TiO2.
[0079] <Pre-reduction of catalyst>
[0080] The process is the same as Example 1 except that 1% Ru / TiO2 is replaced by 2% Ru / TiO2.
[0081] <Degradation of mixed waste plastics>
[0082] The process is the same as Example 1 except that 1% Ru / TiO2 is replaced by 2% Ru / TiO2.
[0083] Example 6
[0084] <Preparation of Ru / TiO2 Catalyst>
[0085] Except for weighing 0.25 g of metal salt RuCl3·H2O according to the metal loading of 5%, the rest is the same as Example 1 to prepare 2 g of catalyst Ru / TiO2.
[0086] <Pre-reduction of catalyst>
[0087] The process is the same as Example 1 except that 1% Ru / TiO2 is replaced by 5% Ru / TiO2.
[0088] <Degradation of mixed waste plastics>
[0089] The process is the same as Example 1 except that 1% Ru / TiO2 is replaced by 5% Ru / TiO2.
[0090] Example 7
[0091] <Preparation of Ru / CeO2 Catalyst>
[0092] Take Ru metal salt RuCl3·H2O as the precursor, weigh 0.05g of metal salt RuCl3·H2O and 2g of oxide carrier CeO2 according to the metal loading of 1%, dissolve the metal salt RuCl3·H2O in 5mL of water, and stir magnetically at 200rpm for 30min to form a precursor solution;
[0093] The rest is the same as in Example 1, and 2 g of catalyst Ru / CeO2 is obtained.
[0094] <Pre-reduction of catalyst>
[0095] Except for replacing Ru / TiO2 with Ru / CeO2, the rest is the same as Example 1.
[0096] <Degradation of mixed waste plastics>
[0097] Except for replacing Ru / TiO2 with Ru / CeO2, the rest is the same as Example 1.
[0098] Example 8
[0099] <Preparation of Ru / SiO2 Catalyst>
[0100] Take Ru metal salt RuCl3·H2O as the precursor, weigh 0.05g of metal salt RuCl3·H2O and 2g of oxide carrier SiO2 according to the metal loading of 1%, dissolve the metal salt RuCl3·H2O in 5mL of water, and stir magnetically at 200rpm for 30min to form a precursor solution;
[0101] The rest is the same as in Example 1, and 2 g of catalyst Ru / SiO2 is obtained.
[0102] <Pre-reduction of catalyst>
[0103] Except for replacing Ru / TiO2 with Ru / SiO2, the rest is the same as Example 1.
[0104] <Degradation of mixed waste plastics>
[0105] Except for replacing Ru / TiO2 with Ru / SiO2, the rest is the same as Example 1.
[0106] Example 9
[0107] <Preparation of Ir / SiO2 Catalyst>
[0108] Taking Ir metal salt IrCl3 as a precursor, 0.033 g of metal salt IrCl3 and 2 g of oxide carrier SiO2 were weighed according to the metal loading of 1%, the metal salt IrCl3 was dissolved in 5 mL of water, and magnetic stirring was performed at 200 rpm for 30 min to form a precursor solution;
[0109] The rest is the same as in Example 1, and 2 g of catalyst Ir / SiO2 is obtained.
[0110] <Pre-reduction of catalyst>
[0111] Except for replacing Ru / TiO2 with Ir / SiO2, the rest is the same as Example 1.
[0112] <Degradation of mixed waste plastics>
[0113] Except for replacing Ru / TiO2 with Ir / SiO2, the rest is the same as Example 1.
[0114] Example 10
[0115] <Preparation of Ru / Al2O3 Catalyst>
[0116] Take Ru metal salt RuCl3·H2O as the precursor, weigh 0.05g of metal salt RuCl3·H2O and 2g of oxide carrier Al2O3 according to the metal loading of 1%, dissolve the metal salt RuCl3·H2O in 5mL of water, and stir magnetically at 200rpm for 30min to form a precursor solution;
[0117] The rest is the same as in Example 1, and 2 g of catalyst Ru / Al2O3 is obtained.
[0118] <Pre-reduction of catalyst>
[0119] Except for replacing Ru / TiO2 with Ru / Al2O3, the rest is the same as Example 1.
[0120] <Degradation of mixed waste plastics>
[0121] Except for replacing Ru / TiO2 with Ru / Al2O3, the rest is the same as Example 1.
[0122] Embodiment 11
[0123] <Preparation of Ir / Al2O3 Catalyst>
[0124] Taking Ir metal salt IrCl3 as a precursor, 0.033 g of metal salt IrCl3 and 2 g of oxide carrier Al2O3 were weighed according to the metal loading of 1%, the metal salt IrCl3 was dissolved in 5 mL of water, and magnetic stirring was performed at 200 rpm for 30 min to form a precursor solution;
[0125] The rest is the same as in Example 1, and 2 g of catalyst Ir / Al2O3 is obtained.
[0126] <Pre-reduction of catalyst>
[0127] Except for replacing Ru / TiO2 with Ir / Al2O3, the rest is the same as Example 1.
[0128] <Degradation of mixed waste plastics>
[0129] Except for replacing Ru / TiO2 with Ir / Al2O3, the rest is the same as Example 1.
[0130] Comparative Example 1
[0131] <Preparation of catalyst Ru / TiO2> and <Pre-reduction of catalyst> are the same as in Example 1.
[0132] <Degradation of mixed waste plastics>
[0133] In a fixed bed reactor (manufacturer: Beijing Zhongshi Yida Technology Co., Ltd., model ZSYD-102), 1 g of the catalyst Ru / TiO2 and 2 g of mixed waste plastics after the above-mentioned pre-reduction treatment were added. Under a hydrogen atmosphere with a pressure of 100 kPa, the fixed bed reactor was heated from room temperature to 200 °C at a rate of 40 °C / min, and then the temperature was stopped and the fixed bed reactor was closed to complete the degradation reaction.
[0134] Comparative Example 2
[0135] <Preparation of catalyst Ru / TiO2> and <Pre-reduction of catalyst> are the same as in Example 1.
[0136] <Degradation of mixed waste plastics>
[0137] In a fixed bed reactor (manufacturer: Beijing Zhongshi Yida Technology Co., Ltd., model ZSYD-102), 1 g of the catalyst Ru / TiO2 and 2 g of mixed waste plastics after the above-mentioned pre-reduction treatment were added. Under a hydrogen atmosphere with a pressure of 100 kPa, the fixed bed reactor was heated from room temperature to 250°C at a rate of 40°C / min, and then the heating was stopped and the fixed bed reactor was closed to complete the degradation reaction.
[0138] Comparative Example 3
[0139] <Preparation of catalyst Ru / TiO2> and <Pre-reduction of catalyst> are the same as in Example 1.
[0140] <Degradation of mixed waste plastics>
[0141] In a fixed bed reactor (manufacturer: Beijing Zhongshi Yida Technology Co., Ltd., model ZSYD-10), 1 g of the catalyst Ru / TiO2 and 2 g of mixed waste plastics after the above-mentioned pre-reduction treatment were added. Under a hydrogen atmosphere with a pressure of 100 kPa, the fixed bed reactor was heated from room temperature to 300 ° C at a rate of 40 ° C / min, and then the temperature was stopped and the fixed bed reactor was closed to complete the degradation reaction.
[0142] The experimental parameters and test results of Examples 1 to 11 and Comparative Examples 1 to 3 are shown in Table 1.
[0143] Table 1
[0144]
[0145] Referring to Table 1, it can be seen from Examples 1 to 11 and Comparative Examples 1 to 3 that although the yield of HCl is high in Comparative Examples 1 to 3, high CH4 yield and high conversion rate cannot be taken into account. When the degradation method of the present application is used to degrade waste mixed plastics, the yields of CH4 and HCl in the examples are high, and the conversion rates are higher than those of the comparative examples. It can be seen from Example 1 that when 1% Ru / TiO2 is used as a catalyst and the degradation step of the present application is used to degrade waste mixed plastics at a programmed temperature of 3°C / min, the yield of CH4 is 80%, the yield of HCl is 99%, and the conversion rate is greater than 95%. This shows that mixed waste plastics can achieve higher degradation efficiency by using the programmed temperature degradation method of the present application without pre-separation.
[0146] The type of catalyst usually affects the degradation of mixed waste plastics. From Examples 1 to 11, it can be seen that when the catalyst in the present application is used, the yield of CH4 is high, the yield of HCl is high, and the conversion rate is high, which indicates that the degradation efficiency of the waste mixed plastics in the present embodiment is high.
[0147] from Figure 1 It can be seen that after 9 cycles of programmed temperature degradation, the waste mixed plastics can still achieve a CH4 yield of nearly 80% and a HCl yield of nearly 90%, and the selectivity of CH4 is nearly 100%. Figure 2 It can be seen that after 9 degradation cycles of 1% Ru / TiO2 at a rate of 40℃ / min from room temperature to 200℃, although the yield of HCl in waste mixed plastics is higher, the selectivity of CH4 is lower than that of 1% Ru / TiO2. Figure 1 The embodiment is relatively poor, and the yield of CH4 is less than 1%. Figure 3 It can be seen that after the catalyst 1% Ru / TiO2 has undergone 9 degradation cycles at a rate of 40°C / min from room temperature to 250°C, although the selectivity of CH4 and the yield of HCl in waste mixed plastics are high, the yield of CH4 is less than 20%. Figure 4 It can be seen that after the catalyst 1% Ru / TiO2 has undergone 9 degradation cycles of heating from room temperature to 300°C at a rate of 40°C / min, although the yield of HCl in the waste mixed plastics is high, the selectivity of CH4 decreases and the yield of CH4 is less than 40%. In summary, the catalyst 1% Ru / TiO2 still has a high reaction activity after 9 cycles of the degradation step of heating according to the present application.
[0148] Based on the above analysis, it can be seen that the degradation of waste mixed plastics by the programmed temperature degradation method of the present application can reduce the poisoning effect of Cl atoms on the catalyst while obtaining high yields of CH4 and HCl, and the catalyst still has high stability and selectivity during the programmed temperature degradation reaction cycle of the present application.
[0149] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for degrading mixed waste plastics, comprising the following steps: (1) After pre-reduction treatment of the catalyst, the catalyst and mixed waste plastics are added into a fixed bed reactor; (2) Under a reducing gas, controlling the temperature of a fixed bed reactor by temperature programming to obtain a degradation product; Wherein, the mixed waste plastics include polyvinyl chloride; the reducing gas includes hydrogen and argon, based on the volume of the reducing gas, the volume percentage of the hydrogen is 10%-100%, and the volume percentage of the argon is 0%-90%; the heating rate of the fixed bed reactor at 150°C-350°C is 1°C / min-5°C / min.
2. The method according to claim 1, wherein: The catalyst is selected from any one of Pt / TiO2, Ru / Al2O3, Ru / TiO2, Ru / CeO2, Ru / SiO2, Ir / Al2O3, Ir / TiO2 or Ir / SiO2.
3. The method according to claim 1, wherein: The catalyst is Ru / TiO2, and based on the mass of TiO2, the loading amount of Ru in the Ru / TiO2 is 0.1%-5%.
4. The method according to claim 1, wherein: The mixed waste plastics include at least one of polyolefin, polystyrene or polyethylene terephthalate.
5. The method according to claim 4, wherein: Based on the mass of the mixed waste plastics, the mass percentage of the polyvinyl chloride is 25%-100%.
6. The method according to claim 1, wherein: The mass ratio of the catalyst to the mixed waste plastics is 1:(1-5).
7. The method according to claim 1, wherein: In step (1), the step of pre-reduction treatment of the catalyst comprises: before using the catalyst, placing the catalyst in a reaction gas at 200° C.-500° C. for reduction for 2 h-6 h; The reaction gas is selected from hydrogen or diluted hydrogen.
8. The method according to claim 7, wherein: The reaction gas is diluted hydrogen. Based on the volume of the diluted hydrogen, the volume percentage of the hydrogen is 10%-90%, and the volume percentage of the argon is 10%-90%.
9. The method according to claim 1, wherein: After step (2), the catalyst is taken out from the fixed bed reactor and reused in step (1).
10. The method according to claim 1, wherein: The pressure of the reducing gas is 50 kPa-150 kPa.
11. The method according to claim 1, wherein: The degradation products include at least one of HCl, CH4, NH3 or H2O.